Cotton fabric: a natural matrix suitable for controlled release systems - Todorova, Snezhana Bogomilova (2007)
The possibility to use cotton as a matrix for controlled release systems was studied by covalently attaching a model compound, specifically the reactive dye Remazol Brilliant Blue R to its surface. Afterwards the fabric was coated with a commercial cellulase. The release of the dye, obtained by the hydrolysis of cotton fibres in sweat buffer, was monitored. The reducing sugars concentration increased for both fabrics (with and without the dye covalently fixed) while the increase in the absorbance was only attained for the dyed cotton, as expected. These results confirm the viability of using cotton as a natural matrix for controlled released systems while presenting a promising approach to immobilize covalently other substances in cotton garments, like fragrances, which could be released by the action of human sweat.